Association between oral microbiome diversity and all-cause mortality: a longitudinal study of NHANES, 2009–2012 - Bo Lin; Liang Zheng; Wanna Chen; Ju Yu; Zhanqiang Zhang; Weiming Lv (BMJ Open)
Objective The study investigates the association between oral microbiome diversity and all-cause mortality.Design Population-based cohort study.Setting US National Health and Nutrition Examination Survey (2009–2010 and 2011–2012).Participants A total of 8224 participants who had valid data on the oral microbiome diversity and survival through 31 December 2019 were included in this study.Primary and secondary outcome measures Oral microbiome diversity was measured using the observed number of amplicon sequence variant (ASV) and grouped into quartiles. Cox proportional hazards regression models were used to estimate the HR and 95% CI for all-cause mortality according to the quartiles of ASV number, adjusted for potential confounders.Results Among the 8224 participants (mean (SD) age: 42.0 (15.1) years; 49.9% male; 37.2% white, 23.8% black, 27.2% Hispanic and 11.8% other race/ethnicity), the median follow-up time was 108 months (IQR, 95–120 months) and 429 (5.2%) deaths were identified. Participants with a higher ASV number were more likely to be poor, non-Hispanic black or Hispanic, uninsured and current smokers, more likely to have poor self-rated oral health and periodontitis and less likely to use dental floss. However, compared with the lowest quartile of the ASV number, a suggestive association was observed for the second quartile (HR=0.80, 95% CI: 0.60 to 1.08), a significant reduction in all-cause mortality was observed for the third (HR=0.55, 95% CI: 0.37 to 0.82) and the fourth (HR=0.58, 95% CI: 0.38 to 0.89) quartile. The dose–response association for all-cause mortality risk was curvilinear; the protective association plateaued when the number of ASVs was larger than 120.Conclusion Despite being linked to greater socioeconomic disadvantages and poorer oral health, higher oral microbiome diversity was significantly associated with a substantial reduction in all-cause mortality.